PENGARUH PEMBERIAN JAMINAN KECELAKAAN KERJA DAN JAMINAN KEMATIAN BPJS KETENAGAKERJAAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. MITSUBISHI KRAMA YUDHA MOTORS & MANUFACTURING - Arief Syah Safrianto (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
In Indonesia the number of occupational accidents shows a fairly alarming number, there are cases of accidents that every day experienced by the workers of every 100 thousand workers. This research aims to analyze the effect of job accident guarantee and death guarantee of BPJS employment on employee productivity at PT Mitsubishi Kramat Yudha Motor and Manufacturing Jakarta, with sample of 97 employees. Adapaun sampling technique used using simple random sampling with SPSS version 18 analysis. The result of this research shows that there is partial influence between work accident to work productivity, there is partial influence between mortality guarantee to work productivity and there is influence between work accident and work death together to work productivity.